Magnetic and transport properties of charge ordered La0.5Ca0.5MnO3 and La0.4Ca0.6MnO3 films - Prokhorov, V.G.; Komashko, V.A.; Kaminsky, G.G.; Lee, Y.P.; Park, S.Y.; Hyun, Y.H.; Svetchnikov, V.L.; Kim, K.W.; Rhee, J.Y. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2005)
The magnetic and the transport properties of La0.5Ca0.5MnO3 and La0.4Ca0.6MnO3 films with different thickness, prepared by rf-magnetron sputtering by using the so-called "soft" (or powder) target on LaAlO3 substrate, have been investigated. The electron-diffraction and the high-resolution electron microscopy (HREM) studies show that the charge-ordered phase is observed at room temperature for all films. Both the paramagnetic-to-ferromagnetic transition at TC ≈ 250 K upon cooling and the appearance of an antiferromagnetic (AFM) phase at TN ≲ 140 K were observed in the La0.5Ca0.5MnO3 films, while the La0.4Ca0.6MnO3 films exhibited the AFM transition only at the same temperature, excepting the small ferromagnetic (FM) response from a "dead" layer. It was shown that the volume fraction of the FM phase in the La0.5Ca0.5MnO3 film did not exceed of and the FM phase coexisted with the AFM one at low temperature. All films manifest an exponential temperature dependence of resistance without evidence of the metal-insulator transition. This is explained by the scarcity of the FM phase for the formation of infinite percolating cluster and by an existence of the charge-ordered phase. The field-dependent magnetoresistance at low temperature is described in terms of the spin-assisted polaron-hopping model.